Effect of Harvesting Stages and Post Harvest Ripening on Seed Yield and Seed Quality of Bottle Gourd var. ABG-1 - DHIMANT DESAI; KALYANRAO; BHUMIT PATEL; N SASIDHARAN (Seed Research, 2026)
An experiment was carried out to investigate the effect of stage of harvest and post harvest ripening on seed yield and quality of bottle gourd cv. ABG-1 during kharif 2014-15. The treatments consisted of three stages of fruit harvest (40, 50 and 60 days after anthesis), three post harvest ripening (PHR) periods (10, 20 and 30 days) and their combinations. Significant increase in fruit length, fruit width, number of filled seed per fruit, seed weight per fruit, seed yield per vine and seed yield per ha were noticed in the fruits harvested at 60 DAA. However, the seed quality parameters were significantly higher in 50 DAA for germination percentage, seedling length, seedling fresh weight, seedling dry weight, vigour index-I, and vigour index-II. The significantly higher seed quality parameters were observed at 20 days of post harvest ripening (PHR) as compared to other treatments. Effect of harvesting stages at 50 DAA and PHR of 20 days gave higher seed yield and seed quality. Hence, it is concluded that Bottle gourd cv. ABG-1 should be harvested at 50 DAA and 20 days PHR for obtaining better quality seeds.